Psychological flexibility and suicide probability in adolescents: An ACT-based intervention study - Aydın, Yunus Emre; Kıran, Binnaz (Anales de Psicología / Annals of Psychology, 2026)
The aim of this study was to investigate whether there is a relationship between suicide probability and psychological flexibility/rigidity in adolescents and to examine the effect of an ACT-based psychoeducation programme developed by the researchers on reducing suicide probability and psychological rigidity in adolescents. Therefore, the study consists of two stages. The first stage was conducted with the relational screening model and the second stage was conducted with the experimental model. Suicide Probability Scale and Acceptance and Action Questionnaire-II were used as data collection tools. The first stage of the study was carried out with 485 students studying in a high school. The second stage was conducted with a total of 24 students from this group who had a high suicide probability. In the study, it was found that there was a positive and moderately significant relationship between adolescents' psychological rigidity levels and suicide probability. In addition, it was concluded that ‘ACT Based Psychoeducation Programme’ was effective on suicide probability, suicide probability sub-dimensions and psychological rigidity levels of adolescents. Improving the psychological flexibility of adolescents is important in terms of preventing many mental health problems, including suicide.